Evaluation of the relationship between phantom position and computed tomography dose index in cone beam computed tomography when assuming breast irradiation - Ueno, Hiroyuki (J Appl Clin Med Phys, 2021)
This study aims to investigate the influence of the phantom position on weighted computed tomography dose index (CTDI(w)) in cone beam computed tomography (CBCT) when assuming breast irradiation. Computed tomography dose index (CTDI) was measured by the x‐ray volume imaging of CBCT using parameters for image‐guided radiation therapy (IGRT) in right breast irradiation. The measurement points of CTDI ranged from 0 (center) to 16 cm in the right–left (RL) direction, and from 0 (center) to 7.5 cm in the anterior–posterior (AP) direction, which assumed right breast irradiation. A nonuniform change exists in the relative value of CTDI(w) when the phantom deviated from the isocenter of CBCT. The CTDI(w) was ~30% lower compared with the value at the isocenter of CBCT when the phantom deviated 7.5 and 16 cm at the AP and RL directions, respectively. This study confirmed the influence of the phantom position on the CTDI values of CBCT. The CTDI measured at the isocenter of CBCT overestimates that measured at the irradiation center of the breast.